OVERVIEW OF THE FIRST 1000 DAYS OF LIFE FOR EXPECTANT MOTHERS AND TODDLERS AGED 0-2 YEARS IN GIANYAR REGENCY, BALI, INDONESIA - Luh Gede Pradnyawati; Dewa Ayu Putu Ratna Juwita (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: The first 1000 days of life are the most critical period in children’s physical and cognitive development. Nutritional status in the first 1000 days of life in expectant mothers and children under five will affect the quality of health, intellectual, and productivity in the future. According to the Basic Health Research of Bali Province, the prevalence of stunting in Bali is 32.6%, with the most cases, one of which is in Gianyar Regency. Objectives: To present an overview of the first 1000 days of life in expectant mothers and toddlers aged 0-2 years. Materials and Methods: This study uses a descriptive research design with a household survey using a cross-sectional approach to 30 clusters. From each selected census block, 5 expectant mothers, 5 toddlers aged 0-1 years and 5 toddlers aged 1-2 years were selected as samples using simple random method from 450 respondents in the total sample. Results: The incidence of stunting in toddlers aged 1 year is 12% and in toddlers aged 2 years is 17% with a total rate of 19% in Gianyar Regency. In terms of gender of those who experience stunting, most of them are female with a percentage of 20%. In the implementation of the first 1000 days of life, especially in the level of achievement of specific interventions, there are expectant mothers who are exposed to cigarette smoke or as passive smokers with a percentage of 42%. At the level of achievement of sensitive indicators, especially the provision of clean water and sanitation, it is found that only 5.1% has access to clean water. Conclusions: There are 19% stunting toddlers in Gianyar Regency. Further research is needed, which adds or expands other variables and develops research methods.